Opiate activation suppresses the drinking, pressor and natriuretic responses induced by cholinergic stimulation of the medial septal area - Haibara, A. S.; Saad, W. A. [UNESP]; Camargo, L. A A [UNESP]; Menani, José Vanderlei [UNESP]; Renzi, Antonio [UNESP]; De Luca, L. A. [UNESP]; Antunes-Rodrigues, J. (Elsevier, 1992)
The present study investigates the participation and interaction between cholinergic and opiate receptors of the medial septal area (MSA) in the regulation of Na+, K+ and water excretion, drinking and blood pressure regulation. Male Holtzman rats were implanted with stainless steel cannulae opening into the MSA. Na+, K+ and water excretion, water intake and blood pressure were measured after injection of carbachol (cholinergic agonist), FK-33824 (an opiate agonist) + carbachol or naloxone (an opiate antagonist) + carbachol into MSA. Carbachol (0.5 or 2.0 nmol) induced an increase in Na+ and K+ excretion, water intake and blood pressure and reduced the urinary volume. FK-33824 reduced the urinary volume and Na+ and K+ excretion. Previous injection of FK-33824 (100 ng) into the MSA blocked the increases in Na+ and K+ excretion, water intake and blood pressure induced by carbachol. Naloxone (10 μg) produced no changes in the effect of 2.0 nmol carbachol, but potentiated the natriuretic effect induced by 0.5 nmol dose of carbachol. These data show an inhibitory effect of opiate receptors on the changes in cardiovascular, fluid and electrolyte balance induced by cholinergic stimulation of the MSA in rats. © 1992.
Keywords: Carbacholl; Cardiovascular responses; Electrolyte excretion; Opiates; Septal area; carbachol; cholinergic receptor stimulating agent; enkephalin[2 dextro alanine 4 methylphenylalanine 5 methioninol sulfoxide]; naloxone; opiate agonist; opiate antagonist; opiate receptor; animal experiment; animal tissue; blood pressure; controlled study; drinking; electrolyte excretion; intracerebral drug administration; male; nonhuman; priority journal; rat; septum nucleus; Analysis of Variance; Animal; Blood Pressure; Brain; Carbachol; Diuresis; Drinking Behavior; Drug Interactions; FK 33-824; Heart Rate; Male; Naloxone; Natriuresis; Rats; Reference Values; Support, Non-U.S. Gov't